Lista doktorek i doktorów wypromowanych przez Profesora Tadeusza Buksińskiego (1995–2014) - Sensus Historiae (Sensus Historiae, 2022)
Lista doktorek i doktorów wypromowanych przez Profesora Tadeusza Buksińskiego (1995–2014)